2021
DOI: 10.3390/molecules26216734
|View full text |Cite
|
Sign up to set email alerts
|

Physical-Mechanical Behavior and Water-Barrier Properties of Biopolymers-Clay Nanocomposites

Abstract: The preparation and characterization of biodegradable films based on starch-PVA-nanoclay by solvent casting are reported in this study. The films were prepared with a relation of 3:2 of starch:PVA and nanoclay (0.5, 1.0, and 1.5% w/v), and glycerol as plasticizer. The nanoclays before being incorporated in the filmogenic solution of starch-PVA were dispersed in two ways: by magnetic stirring and by sonication. The SEM results suggest that the sonication of nanoclay is necessary to reach a good dispersion along… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 48 publications
3
26
1
Order By: Relevance
“…This second area represents the outlet of the plasticizer. This behavior could be explained by the interaction between the CNC and the plasticizer [ 13 , 20 ], or by the barrier effect of CNC that caused a delay in the release of the plasticizer [ 16 ]. Likewise, the degradation temperatures in the range of 255 °C and 365 °C ( Figure 3 b) presented bifurcation due to the degradation of each polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This second area represents the outlet of the plasticizer. This behavior could be explained by the interaction between the CNC and the plasticizer [ 13 , 20 ], or by the barrier effect of CNC that caused a delay in the release of the plasticizer [ 16 ]. Likewise, the degradation temperatures in the range of 255 °C and 365 °C ( Figure 3 b) presented bifurcation due to the degradation of each polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have evaluated the use of nanometric compounds for the reinforcement of materials made from natural polymers. It has been found that reducing the particle size of the reinforcing materials promotes more homogeneous dispersion and increases the specific surface of the reinforcements, such as nanocellulose and nanoclays [ 16 , 17 , 18 , 19 ]. Nanocellulose is produced from cellulose, the most abundant polymer in nature, which can be obtained from the residues of agricultural byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…The film-forming solution was dried in an acrylic mold at 65 • C for 5 h in a convection oven (Oven Series 9000, Thermolyne). The drying process and temperature were determined according to the methodology of Calambas, Heidy Lorena, Abril Fonseca, Dayana Adames, Yaneli Aguirre-Loredo and Carolina Caicedo [6], and Jiménez-Regalado, Enrique Javier, Carolina Caicedo, Abril Fonseca-García, Claudia Cecilia Rivera-Vallejo and Rocio Yaneli Aguirre-Loredo [13]. The composite films were previously conditioned for 48 h at 25 • C and 54% RH before evaluating their physicochemical properties.…”
Section: Preparation Of Filmogenic Solutionsmentioning
confidence: 99%
“…The addition of poly(vinyl alcohol) (PVOH) in starch films improved their mechanical behavior significantly, increasing their elongation by up to 600% [5]. On the other hand, the presence of chitosan improved the hydrophobicity, water vapor barrier, and water adsorption capacity [6]. Because edible films must have characteristics such as flexibility, elasticity, and high mechanical resistance to allow their handling and maintain their physical integrity during their application, the use of plasticizing substances that improve or provide these properties is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The paper of Calambas et al, entitled "Physical-Mechanical Behavior and Water-Barrier Properties of Biopolymers-Clay Nanocomposites", reports on the preparation of novel biodegradable starch-polyvinylalcohol (PVA)-nanoclay nanocomposites films [6]. Different nanofiller amounts were dispersed within the polymer matrix by solvent casting, and the dispersion was performed by magnetic stirring and sonication.…”
Section: The Contribution Of This Special Issuementioning
confidence: 99%